2015
DOI: 10.1111/1365-2664.12531
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the roles of section length and instream habitat enhancement for river restoration success: a field study of 20 European restoration projects

Abstract: 1. Restoration of river hydromorphology often has limited detected effects on river biota. One frequently discussed reason is that the restored river length is insufficient to allow populations to develop and give the room for geomorphological processes to occur. 2. We investigated ten pairs of restored river sections of which one was a large project involving a long, intensively restored river section and one represented a smaller restoration effort. The restoration effect was quantified by comparing each res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 60 publications
5
68
0
4
Order By: Relevance
“…In the 20 restoration projects investigated in REFORM, the effect of restoration on richness and diversity was higher for terrestrial and semi-aquatic compared to aquatic organism groups. Restoration had no or only little effect on species richness or diversity of macroinvertebrates and fish (see Verdonschot et al and Schmutz et al, 2015), while restoration had a clear positive effect on richness or diversity of organism groups inhabiting river banks or adjacent shallow shoreline habitats like ground beetles and macrophytes (see Januschke & Verdonschot as well as Ecke et al, 2015). However, the most floodplain-related organism group (floodplain vegetation) showed no increase in total richness or diversity (see Göthe et al, 2015), in contrast to other studies reporting a significantly higher richness in restored compared to degraded sections (Jähnig et al, 2009;Januschke et al, 2011).…”
Section: Selected Results and Recommendationsmentioning
confidence: 99%
“…In the 20 restoration projects investigated in REFORM, the effect of restoration on richness and diversity was higher for terrestrial and semi-aquatic compared to aquatic organism groups. Restoration had no or only little effect on species richness or diversity of macroinvertebrates and fish (see Verdonschot et al and Schmutz et al, 2015), while restoration had a clear positive effect on richness or diversity of organism groups inhabiting river banks or adjacent shallow shoreline habitats like ground beetles and macrophytes (see Januschke & Verdonschot as well as Ecke et al, 2015). However, the most floodplain-related organism group (floodplain vegetation) showed no increase in total richness or diversity (see Göthe et al, 2015), in contrast to other studies reporting a significantly higher richness in restored compared to degraded sections (Jähnig et al, 2009;Januschke et al, 2011).…”
Section: Selected Results and Recommendationsmentioning
confidence: 99%
“…These efforts inform project-specific management questions but can also, if properly designed and analyzed, provide valuable insights to enhance the efficacy of future assessment and management actions. In this paper, we draw from previous syntheses of river restoration [5][6][7][8][9][10][11][12][13][14] to show how the proper application of scientific approaches can lead to more effective and informative assessment and restoration efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Based on legislative frameworks such as the EU Water Framework Directive (WFD) and the Clean Water Act in the United States, large investments have been made to restore rivers. In Europe, degraded river hydromorphology is considered one of the central impacts to the ecological status of rivers (EEA, 2012;Hering et al, 2015). For example, the German national river habitat survey, which evaluates 31 hydromorphological parameters for 100 m river sections, concluded that the majority of German rivers are severely degraded (Gellert et al, 2014;UBA, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing attention has also been given to the response of floodplain organisms (e.g., Hering et al, 2015;Göthe et al, 2016;Januschke and Verdonschot, 2016), while functional characteristics, i.e., the rates and patterns of ecosystem processes, have rarely been addressed. Ecosystem functions are life-supporting processes that are directly linked to ecosystem services, i.e., the benefits people obtain from the environment (Palmer and Filoso, 2009).…”
Section: Introductionmentioning
confidence: 99%